Attitudes Toward Religion and Believers in China: How Education Increases Tolerance of Individual Religious Differences and Intolerance of Religious Influence in Politics. Issue 1 (2nd January 2020) - Wang, Xiuhua; Froese, Paul
Abstract: Religious repression in China is closely studied, yet there is little research into what the Chinese public thinks about religion. Previously, education is thought to increase empathy, producing a deeper understanding of "the othe"?. In China, the educational system conveys ant-religious ideology of the government, which may foster ant-religious attitudes among highly educated people. Considering these two competing perspectives, we examine the relationship between education and religious tolerance in China. We find that highly educated people are more empathetic of the individual's religious beliefs, but also more certain that religious leaders and institutions should be restricted in their political activities.